Paleozoic Paraná Basin transition from collisional retro-foreland to pericratonic syneclise: Implications on the geodynamic model of Gondwana proto-Andean margin. (November 2021) - Henrique-Pinto, R.; Basei, M.A.S.; Santos, P.R.; Saad, A.R.; Milani, E.J.; Cingolani, C.A.; Frugis, G.L.
Abstract: Providing significant advancements in the knowledge and development of the global plate tectonic theory, the Paraná Basin records a long period of sedimentary accumulation with evidence of substantial climatic and bio-stratigraphic changes throughout most all of the Phanerozoic. Two cycles of sedimentation are identified in the lowermost sequences (Rio Ivaí and Paraná groups), followed by a ~50 Ma gap until the deposition of the early Gondwanic cycle (Itararé Group). The literature suggests that some of those depositional cycles were influenced by episodes of terrane accretion during the amalgamation of the Gondwana Supercontinent. The paleo-topography generated by the Ocloyic orogeny (460-430 Ma) likely resulted in flexural subsidence in the lowermost stratigraphic cycles of the Paraná Basin. In response to dynamic topography, the forebulge probably shifted to a system dominated by long-wavelength propagation developed over a distance of more than 800 km, most likely due to the influence of the subducted oceanic lithosphere of Panthalassa. The presence of Ordovician sources in the pre-Carboniferous sequences supports a provenance of exhumed Famatinian magmatic arc and associated rocks given that Ordovician magmatic activity is not recorded anywhere else in the cratonic regions. Furthermore, important detrital zircon population yielding Cambrian ages, likely derived from Eastern Pampean Range. In additional, the gap between crystallization and depositional ages within the Paraná Basin supports a model that transitions from a collisional retro-foreland basin to a pericratonic syneclise after the deposition of the Paraná Group. Highlights: The Ocloyic orogeny caused a flexural subsidence that controlled the early stages of the Paraná Basin. Ordovician and Cambrian detrital zircon ages support provenance from Famatinian magmatic arc and east Pampean Range. After late Devonian the Paraná Basin changed from a retro-foreland basin to a vast syneclise.